Acid Decomposition of Silver Sulphide Mineral During Pressure Oxidation of Mixed Sulphides - Samuel A. Bolorunduro; David B. Dreisinger; Gus Van Weert (International Mineral Processing Congress, 2003)
"Silver is currently lost as jarosite during the pressure oxidation of sulphides and cyanidation of the residues yields 5-10% of silver. Efforts to recover silver from complex sulphides, which contain economic fractions of silver require an understanding of the behaviour of acanthite during pressure oxidation. However, previous studies of acanthite (Ag2S) reaction have been complicated by the formation of argento-jarosite and uncertainties arise on the interpretation of the results.In this work, the acid pressure oxidation of high-grade natural silver sulphide mineral (acanthite) was carried out at 110-150°C and under the conditions similar to that of pressure oxidation of complex sulphide. The predominant product of reaction is elemental sulphur. The rate of reaction increases with increasing temperature and with the presence of ferric ions. The kinetics is controlled by chemical reaction with activation energy of 72.6 kJ/mol. The rate of reaction decreases with the presence of silver sulphate in the initial slurry. The proposed overall reaction is close to: []"